2019
DOI: 10.3389/fphar.2019.00461
|View full text |Cite
|
Sign up to set email alerts
|

miRNA-218 Targets Lipin-1 and Glucose Transporter Type 4 Genes in 3T3-L1 Cells Treated With Lopinavir/Ritonavir

Abstract: Background: Metabolic complications represent a common and serious problem associated with HIV infection and combined Antiretroviral Therapy (cART). Alterations in body fat distribution are associated with significantly increased risks of (i) metabolic derangements, (ii) cardiovascular pathologies, and (iii) insulin resistance. A case control study showed that in subcutaneous adipose tissue from HIV-infected patients on cART presenting lipodystrophy (LS), the levels of miRNA-218 were upregulated and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 55 publications
(75 reference statements)
2
16
0
Order By: Relevance
“…miR-218-2-3p expression was significantly increased at 2 h upon exposure to a lipid challenge in the duodenum and jejunum of male mice, and in the ileum of females. Recently, via loss and gain of function experiments, Bresciani et al showed that miRNA-218 targets the lipin-1 gene altering its functionality 30 . Members of the Lipin family have a critical role in the regulation of intestinal lipid homeostasis and chylomicron production 31 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…miR-218-2-3p expression was significantly increased at 2 h upon exposure to a lipid challenge in the duodenum and jejunum of male mice, and in the ileum of females. Recently, via loss and gain of function experiments, Bresciani et al showed that miRNA-218 targets the lipin-1 gene altering its functionality 30 . Members of the Lipin family have a critical role in the regulation of intestinal lipid homeostasis and chylomicron production 31 .…”
Section: Discussionmentioning
confidence: 99%
“…(a) Time-course(30,60, 120 and 240 min) expression of miRNAs showing significant differences in response to an oral lipid challenge in male C57BL/6 mice. Data are shown as mean ± SD; n ≥ 7.…”
mentioning
confidence: 99%
“…Indeed, adipogenesis is a process in which there is marked change in the transcription profile. HIV-infection and HAART were reported to alter this profile [ 35 , 36 , 37 ]. Accordingly, many proteins, particularly several secreted factors, are newly synthesized during adipogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…17 HIV-infected patients with lipodystrophy or metabolic abnormalities due to ART have decreased lipin-1 mRNA expression in subcutaneous adipose tissues. 18 In differentiated 3T3-L1 cells, treatments with PIs resulted in reduction in lipin-1 mRNA expression by promoting the miRNA-218 expression. Although the role of miRNA is still ambiguous, it was reported to have a relationship with glucose transporter type 4 (GLUT-4) gene expression which is the insulin-stimulated glucose transporter.…”
Section: In Vitro Studiesmentioning
confidence: 96%
“…3T3-L1 adipocytes on exposure to lopinavir: ritonavir combination showed a significant reduction in lipid (−13.2% in concentration of 12 μM:3 μM and −14.5% in 16 μM:4 μM, P<0.05). 18 Caron et al 19 examined the long-term effects of NRTIs on lipid accumulation and mitochondrial function of differentiating 3T3-F442A and differentiated 3T3 adipocytes. Among the treated NRTIs, zidovudine (1 μM) and stavudine (10 μM) showed changes in lipid phenotype, content, and expression of metabolic markers.…”
Section: In Vitro Studiesmentioning
confidence: 99%